Looking‐glass‐self: Tale of happiness, self‐esteem, and satisfaction with life among transgender from Kinner community. Issue 3 (12th October 2020) - Tiwari, Mansi; Narula, Sumit; Mathur, Garima
Abstract : Social adjustment, and feeling isolated, is one of the critical issues faced by the Hijra's from our society, due to sexual prejudices and stigmas. However, no one bothers how they actually feel, how they see themselves? The idea behind the paper is to identify the impact of looking‐glass self (self‐concept) on happiness, self‐esteem, and satisfaction with life, among transgender from Hijra community, to accentuate the reality of how they feel, what is their self‐concept, and its relationship with the mentioned constructs. The current study was conducted in India; snowball sampling is used to contact the respondents of the mentioned category, and variance‐based structural equation modeling techniques on second‐order construct, using two‐stage approach, were used to study the relationships between the constructs used for the current study. The outcome of the study depicts that there is a presence of significant relationships between the mentioned variables, which show that the respondents are strongly maintaining their self‐concept but that does not mean anyway that they are also happy and enjoying the social treatment given to them. This study is for the social workers, government as well as for the society, who pretends as a flag bearer of quality and promotes diversity in India. It will be an eye‐opener for all those who really want to support such marginalized community as they have already achieved a place in the gender column under the gender category as other "Third Gender." The current study is original and contributes in understanding the truth behind the real journey of the mentioned community. How they feel, what they expect is still untapped; this paper will raise voice for them to contribute in respectful living in Indian society.